Applying Klos Method to Increase the Effective Reading Speed for the 6th Grade Students of Elementary School - Latief, Syekh Adiwijaya; Roslina, Roslina; Nashruddin, Nashruddin (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
This classroom action research aims to identify the improvement of the effective reading speed of the 6th grade students at UPT SPF SDI Mannuruki 2 Makassar, by using klos method, with 20 students as research subjects. The results showed that in the 1st cycle of the learning activity, students who received effective reading speed scores in the low category were 15 (75%), and only 5 students (25%) achieved high effective reading speed. The results of the students’ ability test in the 1st cycle were: (1) 5 students (25%) at independent level; (2) 5 students (25%) at instructional level; (3) 10 students (50%) at frustration level. In the 2nd cycle, the number of students who received effective reading speed score in the low category remained 1 student (5%), and those who received high effective reading speed score were 19 students (95%). Besides that, in the term of students’ ability, 19 students (95%) were at independent level, 1 student (5%) were at instructional level, and no students were at frustration level. Therefore, it can be said that the ability of students in reading speed with the klos method has increased significantly.